PENGEMBANGAN BAHAN AJAR SEJARAH TENTANG BIOGRAFI RADEN INTEN II UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA NEGERI 2 SEKAMPUNG TAHUN 2015/ 2016 - Hartono, Febri; Rulianto, Rulianto (Jurnal Santiaji Pendidikan (JSP), 2017)
This research development aims to produce an effective learning media which is more effective to fulfil the needs of teachers and students in the teaching and learning process in schools. Learning Media which was produced in the form of teaching materials in the subject history. The teaching material is about the biography of Raden Inten II to improve critical thinking skills and strengthening the character of the students in SMAN 2 Sekampung.This type of research is to develop the teaching media using a model ADDIE (Analysis, Design, Development, Implementation , Evaluation) . Population in this research is class XI IPS SMAN 2 Sekampung. The sample of this study is implemented in three classes, they were class XI IPS 1 as an experimental class, a class XI IPS 2 as the control class, and class XI IPS 3 as the trials class.The results showed that: (1) the teaching media of history at SMAN 2 Sekampung used is student worksheets, handbook and textbooks; (2) teaching materials of history in high school about the biography of Raden Inten II made through model of ADDIE and generate materials teaching media to form a module that has undergone numerous revisions and has been validated by the experts of media and the expert of materials and subsequently successfully tested in the classroom of XI IPS 3 SMAN 2 Sekampung, (3) test of the effectiveness in teaching material history of biography Raden Inten II is done by comparing the value of post-test experimental class and control class with a significance level of 5% and result of students’ ability to have critical think. It was proved from thit 3,700> 2,756 ttab and the strengthening of character with thit 4,168> 1,697 ttab. Therefore, H0 is rejected. It can be concluded that the teaching media of history in the form of teaching materials about the history of biography Raden Inten II is effective to improve critical thinking skills and strengthening the character of the students SMAN 2 Sekampung.